Enhancing thermal comfort: a comprehensive review of wearable cooling systems - Waseem Raza; Arianna Berto; Marco Tancon; Lorenzo Moro; Marco Azzolin (Next Materials)
Exposure to hot environments can induce physiological thermal strain in the human body, leading to reduced working endurance, impaired performance, and an elevated risk of heat-related illnesses. Activities such as sports, military training, and physically demanding work like firefighting can worsen these conditions. The increasing demand for energy-efficient solutions and diverse application requirements has driven the development of wearable cooling systems. These systems offer a localized and efficient alternative to conditioning entire environments, especially for individuals working outdoors or in settings where traditional air conditioning is impractical. This review provides a comprehensive overview of wearable cooling systems, covering their operating principles, designs, testing methodologies, applications, benefits, challenges, and classifications. Wearable cooling systems have been categorized into active, passive, and hybrid types, employing various cooling mechanisms, including air cooling, liquid cooling, vapor-compression cycle cooling, thermoelectric cooling, gas cooling, vacuum desiccant cooling, evaporative cooling, phase change materials, and conductive and radiative textile-based cooling. The review assesses these technologies based on cooling capacity, weight, and operating time, offering a rationale for their selection. Additionally, insights into future research opportunities in wearable cooling systems are discussed, emphasizing the need for continued innovation to enhance thermal comfort and safety.